Sistem Pemantauan Kemajuan Skripsi dengan Visualisasi Timeline-Milestones untuk Skripsi Tepat Waktu: Pendekatan Manajemen Waktu - Rahmi, Rahmi; Djuanda, Djuanda; Samsuar, Samsuar; Anzora, Anzora; Aryani, Irma; Susanti, Nelia (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
A thesis is a mandatory final assignment for undergraduate students, however its compiling process often presents challenges. Especially in terms of time management and progress monitoring. Students struggle to systematically plan the stages of their thesis. While lecturers have difficulty monitoring progress effectively. Therefore, a system is needed to assist both students and lecturers. The aim of this research is to develop a web-based thesis monitoring system with timeline and milestones visualization. This study employs a project management-based time management approach and uses the Waterfall system development model. The requirement analysis stage uses the PIECES framework, while the system design stage includes use case and activity diagrams, followed by implementation through coding and testing with black-box testing. Our research results is a prototype of web-based thesis monitoring system featuring timeline and milestone visualization. This visualization provides a clear overview of a thesis progress, making it easier for students to understand the entire process and for lectures to monitor progress effectively. The testing results show that the prototype system runs well. This system is expected to enhance the effectiveness of the thesis preparation process, support timely completion, and address challenges in monitoring the progress of thesis at universities.